Fifth metatarsal fractures – Is routine follow-up necessary?. Issue 8 (August 2015) - Ferguson, K.B.; McGlynn, J.; Jenkins, P.; Madeley, N.J.; Kumar, C.S.; Rymaszewski, L.
Abstract Background Fifth metatarsal fractures are common, and the outcome with conservative treatment is generally very satisfactory. Operative treatment is only used for selected injuries, particularly stress fractures. Traditionally these patients are routinely reviewed at a fracture clinic, mainly due to the perceived risk of non-union with a Jones' fracture. In 2011 we introduced a standardised protocol to promote weight bearing as pain allowed with an elasticated support or a removable boot. Patients were discharged with structured advice and a help-line number to access care if required, but no further face-to-face review was arranged. More complex cases were reviewed at a "virtual clinic." Our hypothesis was that the introduction of this standardised protocol would be safe, patient-centred and significantly reduce unnecessary outpatient clinic review. Patients and methods We audited fracture clinic attendance and outcomes 1 year before and 1 year after the protocol was introduced in 2011. All radiographs taken at the Emergency Department (ED) presentation were reviewed and classified independently for validation. Results From 2009 to 2010, 279 patients who presented to the ED with fifth metatarsal fractures were referred to a fracture clinic. Of these 279 patients, 267 (96%) attended the fracture clinic, resulting in an overall total of 491 outpatient attendances. Three (1%) were treated operatively for delayed/non-union. From 2011 to 2012, 339 patients presented to the ED with fifth metatarsal fractures – only 67 (20%) were referred to a fracture clinic. 62 (18%) attended clinic appointments with 102 appointments in total. Five (1%) required operative intervention. Conclusion Our study showed no added clinical value for routine outpatient follow-up of fifth metatarsal fractures. Patients can be safely discharged and allowed to bear weight at the time of initial ED presentation if they are provided with appropriate information and ready access to experienced fracture clinic staff.